Remote Surveillance: The Evolution of RF Controlled Spy Robots with Night Vision - Suchitra Jagtap; Sakshi Mate; Shamal Shrikhande (International Journal of Radio Frequency Innovations, 2024)
The project described in this paper will use an RF transmitter and receiver to enable remote control of the robot, enabling users to navigate different terrains and collect visual data. Even in complete darkness, the night vision camera will record crisp pictures and movies, giving you important new information about your surroundings. The robot is ideal for covert surveillance operations due to its small size and agility. An ESP32 microcontroller, a night vision Wi-Fi camera, push buttons, an RF module (transmitter and receiver), a 7809-voltage regulator, a motor driver IC, DC motors, and batteries are used in an RF-controlled spy robot with a night vision camera. The robot can record video in low light and can be operated remotely via an RF remote control. It is operated by an RF remote control and has the ability to record video in low light. The robot's central processing unit, or ESP32 microcontroller, gets instructions from the RF receiver and transmits them to the motor driver IC, which regulates the robot's wheel movements. By streaming video footage to a connected device, the night vision Wi-Fi camera enables the operator to keep an eye on the robot's surroundings
Keywords: ESP32; Night Vision Camera; RF Control; Spy Robot; Wifi